2023
DOI: 10.3390/methane2010002
|View full text |Cite
|
Sign up to set email alerts
|

Fisher–Tropsch Synthesis for Conversion of Methane into Liquid Hydrocarbons through Gas-to-Liquids (GTL) Process: A Review

Abstract: The interest in Gas-to-Liquid technology (GTL) is growing worldwide because it involves a two-step indirect conversion of natural gas to higher hydrocarbons ranging from Liquefied Petroleum Gas (LPG) to paraffin wax. GTL makes it possible to obtain clean diesel, naphtha, lubes, olefins, and other industrially important organics from natural gas. This article is a brief review discussing the state-of-the-art of GTL, including the basics of syngas manufacturing as a source for Fischer-Tropsch synthesis (FTS), hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Regarding NH 3 -TPD profiles, a large desorption peak between 90 and 460−510 °C for all the catalytic materials was observed similarly to the pristine support, suggesting the presence of acid sites with different strengths (see Figure S13b in the Supporting Information), taking into account the acid− base properties of apatite materials due to the presence of functional groups such as Ca 2+ , PO 4 3− , HPO 4…”
Section: Characterization Of the Prepared Ni-based Catalytic Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding NH 3 -TPD profiles, a large desorption peak between 90 and 460−510 °C for all the catalytic materials was observed similarly to the pristine support, suggesting the presence of acid sites with different strengths (see Figure S13b in the Supporting Information), taking into account the acid− base properties of apatite materials due to the presence of functional groups such as Ca 2+ , PO 4 3− , HPO 4…”
Section: Characterization Of the Prepared Ni-based Catalytic Materialsmentioning
confidence: 98%
“…3 However, since the downstream uses of syngas usually requires much lower temperatures (e.g. Fischer− Tropsch synthesis operating at 220−350 °C, 4 methanol synthesis at temperatures ranging from 90−350 °C, 5 or water−gas shift reaction at 200−450 °C), 6 the syngas generated from SMR units should be cooled down, requiring heat exchangers, which usually engender considerable heat loss. As recently reported, among the different alternative solutions to SMR, tri-reforming of methane (TRM) appears as the best option for syngas production from methane (eq 1).…”
Section: Introductionmentioning
confidence: 99%
“…A heterostructure transformer oil based on natural gas oil production technology (i.e., GTL) appeared in 2013 [17] . GTL is produced from hydrocarbons extracted from natural gas and is based on Fischer-Tropsch synthesis technology, making it a potential alternative to traditional mineral oil [18] . Due to the abundance of natural gas reserves, the widespread application of the new GTL is expected to solve the future shortage of high-quality transformer oil supply.…”
Section: Molecular Composition Of Gtl and Mineral Oilmentioning
confidence: 99%
“…Another study demonstrated that a zirconium-based catalyst improved the conversion of syngas to liquid fuels in Fischer-Tropsch synthesis. [114][115][116][117] The aforementioned studies highlighted the potential of zirconium-based catalysts in gasifying biomass to produce high-quality biofuels. Nonetheless, more research is necessary to refine these techniques and establish sustainable, and cost-effective processes for converting energy from biomass via gasification.…”
Section: Gasificationmentioning
confidence: 99%